Precancer exercise capacity and metabolism during tumor development coordinate the skeletal muscle–tumor metabolic competition - Brooks P. Leitner; Andin E. Fosam; Won D. Lee; Kaylee Zilinger; Susana C. B. R. Nakandakari; Xinyi Zhang; Rafael C. Gaspar; Wanling Zhu; Curtis J. Perry; Joshua D. Rabinowitz; Rachel J. Perry (Proceedings of the National Academy of Sciences, 2025)
Higher exercise capacity and regular exercise training improve cancer prognosis at all stages of disease. However, the metabolic adaptations to aerobic exercise training that mediate tumor–host interactions are poorly understood. Here, we demonstrate that voluntary wheel running slows tumor growth and repartitions glucose uptake and oxidation to skeletal and cardiac muscle and away from breast and melanoma tumors in mice. Further, prehabilitation induces repartitioning of glucose metabolism in obese mice: Uptake and oxidation of glucose are enhanced in skeletal and cardiac muscle, and reduced in tumors. These increases in muscle glucose metabolism and reductions in tumor glucose metabolism, correlated with slower tumor progression. Using [U- 13 C 6 ] glucose infusion, we show that exercise increases the fractional contribution of glucose to oxidative metabolism in muscle while reducing it in tumors, suggesting that aerobic exercise shifts systemic glucose metabolism away from the tumor microenvironment and toward metabolically active tissues. Transcriptional analysis revealed downregulation of mTOR signaling in tumors from exercised mice. Collectively, our findings suggest that voluntary exercise may suppress tumor progression by enhancing host tissue glucose oxidation and limiting tumor glucose availability, supporting a model in which exercise-induced metabolic competition constrains tumor energetics.